"Only intelligent attendants need apply": the history of Western Australia's first asylum at Fremantle (1865–1909). (April 2022) - Maude, Phil
Objective: To examine the history of Fremantle, Western Australia's first purpose-built asylum. Method: A range of primary sources were consulted. Results: Fremantle was opened in 1865 to house inmates away from the populace and for the most part under the care of Dr HC Barnett. Attendants as well as inmates were occupied with work roles that kept the asylum functioning cost effectively. Conclusion: Within 15 years, the structure was neglected and overcrowded. Changes to the Penal Servitude Act limiting convict transportation, petty crime and a need to manage its proliferation resulted in large numbers of people being incarcerated at Fremantle.